Understanding user needs: Persona creation for waterpoint monitoring system in Ethiopia - Lopez Astudillo, Sebastian; Gebre, Liyuneh; Teshome, Sintayehu Alemayehu; Nasayo Valverde, Carlos Mario; Dejene, Sintayehu Workeneh; Tesfaye, Lidya Ayalew; Zapata Caldas, Emmanuel; Ortiz Crespo, Berta; Sotelo, Steven (2023)
This document presents an exploration of waterpoint monitoring in Ethiopia through the approach of human-centered design. Utilizing personas, we delve into the diverse goals, challenges, and motivations of stakeholders involved in waterpoint monitoring initiatives across Oromia in Ethiopia. These personas serve as valuable tools for understanding the requirements of users, facilitating informed decision-making, and fostering the development of solutions tailored to the specific needs of Ethiopian communities. By prioritizing empathy and user-centricity, this study aims to enhance the effectiveness and sustainability of waterpoint monitoring efforts in Ethiopia, ultimately contributing to the advancement of water resource management and community well-being in the region.